Epidemiological and clinical implications in Kidney Transplantation of occult Hepatitis C virus infection - Olea T1; Castillo I2; Jiménez C1; Díez J3; Bartolomé J2; Santana MJ1; López- Oliva MO1; González E1; Selgas R1; Carreño V2 (Archives of Clinical Nephrology - Peertechz Publications, 2019)
Occult Hepatitis C virus (HCV) infection (OCI) is characterized by the presence of HCV-RNA in liver or in peripheral blood mononuclear cells (PBMC) in the absence of serological markers. HCV infection in kidney transplant (KT) recipients is associated with lower patient and graft survival. However, the relationship between KT outcome and OCI is unknown. Our aim was to determine in KT recipients the prevalence, risk factors for OCI, and its prognostic implications. We tested 149 adults KT recipients for the presence of OCI. HCV-RNA was tested by a RT-PCR in PBMC and in 2 ml of plasma after ultracentrifugation. OCI was positive in 21 patients (14.1%). Previous blood transfusion was a risk factor for acquiring OCI (p=0.044). Although there were no statistical differences in clinical complications post-KT and in the immunosuppression, graft and patient survival were worse in the OCI positive group (p=0.02 and p=0.04, respectively). In summary, there was a high prevalence of OCI in our KT population with previous blood transfusion as the main risk factor. Long-term graft and patient survival were reduced as compared to OCI negative recipients although the contribution of particular co-morbidities did not reach statistical signifi cance.